User-centered designs for electronic commerce web portals - Robert Jeyakumar Nathan; Norazah Mohd Suki (IGI Global, 2013)
Websites connect businesses with customers. They are an important medium that facilitates online transactions, a necessity for businesses. The design and usability of an Electronic Commerce (EC) website play an important role in achieving its objectives (Kumar, Smith, & Bannerjee, 2004; Marcus, 2005; Nielsen, 2003; 2005; Krug, 2006; Cappel & Huang, 2007). Recognizing their importance, design and usability aspects of EC websites have been widely researched in both applied and academic research (Lecerof & Paterno, 1998; Lohse & Spiller, 1999; Nielsen, 2000; Cao, Zhang, & Seydel, 2005; Flavian & Guinaliu, 2006; Nathan, Yeow, & Murugesan, 2008; Nathan & Yeow, 2009; Robins & Holmes, 2008). This chapter discusses the recent work with web design and electronic commerce. The importance of usability and user-centered web designs are highlighted. Usability to specific target groups and industries, such as airlines, government, and services portals, are also discussed. Altogether, design guidelines are given for web industries, and recommendations are made for better usability in designing websites.